2015
DOI: 10.17507/tpls.0505.04
|View full text |Cite
|
Sign up to set email alerts
|

Refusal and Politeness Strategies in Relation to Social Status: A Case of Face-threatening Act among Indonesian University Students

Abstract: Abstract-The present study aimed at investigating how Indonesian students refuse offers, invitations, and suggestions to persons having different social statuses. Refusal and politeness strategies were the focus of this study. The social variable involved in this study was the social status represented in lower to higher socialstatus (LHSS), higher to lower social-status (HLSS), and equal social-status (ESS) relationships. The data were obtained through discourse completion test (DCT) distributed to 161 studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 2 publications
(3 reference statements)
4
22
0
Order By: Relevance
“…[15] proposed that hesitant is a non-verbal refusal act but the way Silena responded Percy is clearly hesitating. Therefore, this could be a new finding to what [16] proposed. Moreover, the translation is in the same strategy.…”
Section: Avoidancementioning
confidence: 58%
“…[15] proposed that hesitant is a non-verbal refusal act but the way Silena responded Percy is clearly hesitating. Therefore, this could be a new finding to what [16] proposed. Moreover, the translation is in the same strategy.…”
Section: Avoidancementioning
confidence: 58%
“…Al-Mahrooqi and Al-Aghbari (2016) investigated the refusal strategies among Omani EFL students, Abarghoui (2012) who analyzed a comparison of refusal strategies used by Iranians and Australians and Guo (2012) who explored a comparison of refusal strategies used by Chinese and American. With regard to studies refusal in Indonesia, Aziz (2000 as cited in Muniroh, 2013) observed that the study of refusal is based on the trend of Indonesians who do not speak openly, preferring to express their feeling, thoughts and ideas indirectly which is confirmed by others such as Septiany (2013) ;Chojimah, (2015); Nurweni, Sudirman and Mahpul, (2016).…”
Section: Introductionmentioning
confidence: 92%
“…Fraser and Nolen, cited in Watts, Ide and Ehlich (1992), suggested that politeness is the result of a conversational contract by the participant in an effort to maintain socio-communicative interaction, which is free of conflict. In Indonesian context, for instance, Aziz (2000, as cited in Chojimah, 2015) mentioned four values in the Principle of Mutual Consideration, namely a) Harm and Favor Potential, which reminds us to be careful in uttering expressions since they are potentially either to harm or favor others; b) Shared-feeling Principle, which reminds us that our addressee has the same feeling as we do; c) Prima Facie Principle, which stresses the importance of impression in the first sight since it is the point at which our addressee evaluates our politeness manner, and; d) Continuity Principle, which suggests that the continuity of our communication is dependent on the present communication.…”
Section: -34mentioning
confidence: 99%